FROM SHARIA POLITICS TO POLITICAL SHARIA: Towards Democratic Elections Based on the Qur'an - Al-Banjari, Husin M (Universitas Padjadjaran, 2024)
Ibn Taimiyah (1263-1328) in his work as-Siyasah asy-Syar'iah has marked Islamic Politics with